Bioenergy agroecosystems as a basis for food sustainability - Tarariko Yurii; Knysh Vladyslav; Sapaev Ibrokhim (BIO Web of Conferences)
The article examines the prospects for the introduction of a bioenergy system of agricultural production in Western Polesie using the example of a reclaimed area of 10 thousand hectares, under the jurisdiction of the Shatsk Department of Reclamation Systems (Volyn region, Ukraine). A multi-option simulation of the potential sectoral structure of this region was conducted using the “Agroecosystem” software package. The study assessed the key components of the agri-resource potential of the region, identified conditions for improving its efficiency, and proposed sustainable models for sectoral development based on bioenergy principles. A comparative computer analysis showed that the most promising scenario includes organic farming, high-yield dairy production, and the processing of raw materials into dairy and meat products, oil, and flax fiber. Energy needs are met through biogas production from all agricultural waste, which is fully sanitized. The application of biological crop protection systems and energy self-sufficiency reduces production costs by 30%, while the quality and market value of high-end food products increase accordingly. As a result, agricultural profitability rises significantly, and the local population benefits from affordable, high- quality food and products made from natural raw materials. In the future, an important part of the profit could come from reducing greenhouse gas emissions.